Pengaruh Inflasi, Tingkat Suku Bunga dan Nilai Tukar Terhadap Indeks Harga Saham Gabungan (IHSG) Bursa Efek Indonesia - Muhammad Daffa Z (Journal of Business & Management, 2023)
The Influence of Inflation, Interest Rates, and Exchange Rates on the Composite Stock Price Index in the Indonesia Stock Exchange. The purpose of this study is. This study aims to determine the effect of inflation, interest rates and exchange rates on the Composite Stock Price Index in the Indonesia Stock Exchange. The population used in this study is 120 samples, using a purposive sampling technique with criteria set by the author. The analysis used is a multiple linear regression analysis methods. Based on the test results simultaneously, it is found that the variables of Inflation, Interest Rates, and Exchange Rates simultaneously have a positive effect on the Composite Stock Price Index on the Indonesia Stock Exchange. Also, partial inflation, interest rates and Exchange rates positively affect the Composite Stock Price Index on the Indonesia Stock Exchange.